Relation between critical power and functional threshold power - Karsten, A. (Journal of Science and Cycling, 2017)
Introduction: Critical power (CP) provides a valid and reliable testing method (1) to monitor changes in endurance fitness (2). CP is defined as an exercise intensity that can be maintained for prolonged periods of time, typically for 45 to 60 min (3). Whilst having attracted a high level of research interest, to-date even though available as a field test (4-6), it is not widely adopted by coaches. Functional Threshold Power (FTP) on the other hand, whilst being popular in recreational cycling (7) is not well researched. FTP has been defined as the highest average power output (PO) that can be maintained for 60 min (8). CP testing requires multiple exhaustive trials which might explain the apparent gap between research and real-world cycling whilst FTP can be determined from a single maximal 20 min effort. However, FTP to-date has not been validated. Given the potential similarity, the present study investigated the relationship between CP and FTP. We hypothesized non-significant differences between CP and FTP values and a high level of agreement.